2016
DOI: 10.3934/dcdsb.2016047
|View full text |Cite
|
Sign up to set email alerts
|

Controlling stochasticity in epithelial-mesenchymal transition through multiple intermediate cellular states

Abstract: Epithelial-mesenchymal transition (EMT) is an instance of cellular plasticity that plays critical roles in development, regeneration and cancer progression. Recent studies indicate that the transition between epithelial and mesenchymal states is a multi-step and reversible process in which several intermediate phenotypes might coexist. These intermediate states correspond to various forms of stem-like cells in the EMT system, but the function of the multi-step transition or the multiple stem cell phenotypes is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…This suggests that MINC may be a general phenomenon related to the existence of intermediate states and probably exists in other GRNs. Computational simulations of epithelial-mesenchymal transitions (EMTs) recently has shown that increased numbers of intermediate states attenuate noise in cellular fate decisions ( Ta et al., 2016 ), which is analogous to our predictions of how pooling in the intermediate state reduces noise. Primed lineages in hematopoietic stem cells can be represented as an intermediate state with reversible changes, which could explain data showing mean-independent noise attenuation due to a lineage commitment factor ( van Galen et al., 2014 ).…”
Section: Discussionsupporting
confidence: 71%
“…This suggests that MINC may be a general phenomenon related to the existence of intermediate states and probably exists in other GRNs. Computational simulations of epithelial-mesenchymal transitions (EMTs) recently has shown that increased numbers of intermediate states attenuate noise in cellular fate decisions ( Ta et al., 2016 ), which is analogous to our predictions of how pooling in the intermediate state reduces noise. Primed lineages in hematopoietic stem cells can be represented as an intermediate state with reversible changes, which could explain data showing mean-independent noise attenuation due to a lineage commitment factor ( van Galen et al., 2014 ).…”
Section: Discussionsupporting
confidence: 71%
“…That is, the more intermediate EMT states in one cancer type, the better the chance it will metastasize. A complementary feature of multiple intermediate phenotypes was reported to stabilize the cancer stem cell population [51]. Thus, the malignancy level can be quantified by the number of potential intermediate EMT states.…”
Section: Discussionmentioning
confidence: 99%
“…Models have predicted that multiple ICSs can facilitate the attenuation of fluctuating cell populations [ 74 ]. By absorbing some of the noise, these additional states serve as ‘buffers’ against environmental fluctuations, thereby preventing imbalances of cells in terminal states.…”
Section: Possible Functions Of Intermediate Statesmentioning
confidence: 99%